Adult-onset hypogonadotropic hypogonadism caused by aberrant expression of aromatase in an adrenocortical adenocarcinoma - Advani, Andrew; Johnson, Sarah J.; Nicol, Moira R.; Evans, Dean B.; Papacleovoulou, Georgia; Vaikkakara, Suresh; Quinton, Richard; Mason, J. Ian (ENDOCRINE JOURNAL, 2010)
Estrogen-secreting adrenal cancers are extremely rare, with feminizing symptoms attributed to aromatase expression in the adrenal tumor. We describe a case of hypogonadotropic hypogonadism as a consequence of aberrant aromatase expression in a patient with adrenocortical adenocarcinoma. A 54 year-old man presented with a two month history of gynecomastia and reduced libido. Endocrine biochemistry at presentation showed hypogonadotropic hypogonadism (LH 2.4 U/L, FSH <1.0 IU/L, testosterone 2.8 nmol/L) with increased serum estrone (E1, 821 pmol/L) and estradiol (E2, 797 pmol/L) and subclinical ACTH-independent hypercortisolism (serum cortisol post 1mg overnight dexamethasone suppression test, 291 nmol/L). A right adrenal mass was identified on CT scanning and the patient underwent an open adrenalectomy. Post-operative evaluation showed normalization of serum levels of E1 (95 pmol/L), E2 (109 pmol/L), testosterone (11.4 nmol/L), LH (4.1 U/L) and FSH (5.9 IU/L), and of cortisol dynamics. Immunohistochemistry of the adrenal cancer confirmed aberrant expression of aromatase in most, although not all, carcinoma cells. Transcripts associated with utilization of promoters II, I.1 and I.3 were prominently represented in the tumor aromatase mRNA. This case highlights that clinical features of feminizing adrenocortical carcinomas can be secondary to estrogen production by aberrantly transcribed and translated aromatase within the tumor. Even in males, gonadotropin secretion is subject to predominantly estrogen-mediated feedback-inhibition. The diagnosis of adrenocortical adenocarcinoma should be considered in men presenting with low testosterone and gonadotropins, particularly in the presence of feminizing features.